2018
DOI: 10.15625/2525-2518/55/1b/12097
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Curcumin Loaded Nano Polycaprolactone/Chitosan Nonwoven Fabric via Electrospinning Technique

Abstract: Cucurmin loaded poly ε-caprolactone/chitosan (PCL/CTS) nanoscale nonwoven fabric was successfully fabricated using electrospinning, a facial and efficient method. The surface tensions of PCL/CTS blend solutions in various ratios were measured to evaluate the influence of PCL/CTS ratio on fibers formation. The effects of process parameter such as the applied voltage, tip-collector distance and the solution flow rate on the fiber generation and morphology of final fiber were optimized. Nanofibers morphology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…As already shown in the photographic images of the blend fibers, free droplets are observed around the fiber mat containing 10 wt% Cur. A similar trend was observed for the diameter of curcumin-loaded PCL/chitosan [30], polyurethane [20] and cellulose acetate [14] fibers. The resultant thicker fibers with the addition of curcumin were attributed to the higher viscosity of the electrospinning solution and lower solvent evaporation rate.…”
Section: Effect Of Pu and Cur Concentrationsupporting
confidence: 82%
See 1 more Smart Citation
“…As already shown in the photographic images of the blend fibers, free droplets are observed around the fiber mat containing 10 wt% Cur. A similar trend was observed for the diameter of curcumin-loaded PCL/chitosan [30], polyurethane [20] and cellulose acetate [14] fibers. The resultant thicker fibers with the addition of curcumin were attributed to the higher viscosity of the electrospinning solution and lower solvent evaporation rate.…”
Section: Effect Of Pu and Cur Concentrationsupporting
confidence: 82%
“…Fallah et al [32] showed that PCL/gelatin/curcumin nanofibers have an increasing diameter with the increasing voltage ranging from 10 to 20 kV. In another example, Hoang et al [30] reported the increased diameter of PCL/chitosan fibers with respect to the applied voltage (15,18, and 24 kV), pointing out the higher electrostatic force results in the multi-jet formation, hence the multiple fibers can stick each other and form thicker fibers. It can be noted that applied voltage affects not only the fiber diameter but also the hydrophilicity of the fibers, as shown by the contact angle values.…”
Section: Effect Of Electrospinning Parameters On the Pu/cur Fibersmentioning
confidence: 99%
“…Minh Son Hoang and co-authors 27 successfully obtained curcumin-loaded polycaprolactone/chitosan (PCL/CTS) nanofibers which have a diameter range from 267 nm to 402 nm. The authors analyzed in detail the physical characteristics of PCL/CTS spinning polymer solutions, as well as the effect of the technological parameters on solution electrospinnability and fiber morphology.…”
Section: Polymers Used For Curcumin-loaded Fiber Formationmentioning
confidence: 99%
“…More curcumin would be expected to release with a specific rate from higher concentrations, such as 17% curcumin loaded poly (εcaprolactone) (PCL) nanofibers than the lower concentrations, such as 3% curcumin loaded PCL nanofibers, after 12 h (as shown in figure 2(b)) [30]. Using PCL-curcumin solutions, biofunctional electrospun nanofibers were prepared [30][31][32][33]68]. Hoang et al [68] fabricated curcumin loaded PCL/chitosan nonwoven mats (for wound dressings) using formic acid and acetone together as solvents while electrospinning nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…Using PCL-curcumin solutions, biofunctional electrospun nanofibers were prepared [30][31][32][33]68]. Hoang et al [68] fabricated curcumin loaded PCL/chitosan nonwoven mats (for wound dressings) using formic acid and acetone together as solvents while electrospinning nanofibers. They also investigated the release of curcumin (via an in vitro approach) from nonwoven mats of these fibers (having fiber diameters in the range between 267 nm to 402 nm); it was found to be nearly 80% during the initial 100 h. The gelatin nanofibers were found to serve as vehicles to release the drugs in controlled manner.…”
Section: Introductionmentioning
confidence: 99%